2021
DOI: 10.1002/humu.24285
|View full text |Cite
|
Sign up to set email alerts
|

A bi‐allelic loss‐of‐function SARS1 variant in children with neurodevelopmental delay, deafness, cardiomyopathy, and decompensation during fever

Abstract: Aminoacyl‐tRNA synthetases (aaRS) are ubiquitously expressed enzymes responsible for ligating amino acids to their cognate tRNA molecules through an aminoacylation reaction. The resulting aminoacyl‐tRNA is delivered to ribosome elongation factors to participate in protein synthesis. Seryl‐tRNA synthetase (SARS1) is one of the cytosolic aaRSs and catalyzes serine attachment to tRNASer. SARS1 deficiency has already been associated with moderate intellectual disability, ataxia, muscle weakness, and seizure in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…We, therefore, concluded that the variant c.397C>T, p.(Arg133Cys) in WARS1 leads to a, possibly incomplete, loss of function. This observation is in line with other reports in the literature, which have shown that biallelic mutations in ARS genes confer loss-of-function effects (Botta et al, 2021;Friedman et al, 2019;Helman et al, 2021;Mendes et al, 2020;Ravel et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We, therefore, concluded that the variant c.397C>T, p.(Arg133Cys) in WARS1 leads to a, possibly incomplete, loss of function. This observation is in line with other reports in the literature, which have shown that biallelic mutations in ARS genes confer loss-of-function effects (Botta et al, 2021;Friedman et al, 2019;Helman et al, 2021;Mendes et al, 2020;Ravel et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The phenotype observed in individual 5 closely resembles that described by Musante et al, who found the homozygous variant c.514G>A, p.(Asp172Asn) in four individuals from a consanguineous Iranian family who suffered from a severe neurodevelopmental disorder with microcephaly and epilepsy (Table 2) (Musante et al, 2017). Epileptic encephalopathy and neurodevelopmental abnormalities have also been described for four individuals from a consanguineous family in whom the homozygous variant c.638G>T; p.(Arg213Leu) in SARS1 was identified (Ravel et al, 2021; Thevenon et al, 2016). Microcephaly was not a feature in this family.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, WES identified for the first time a de novo variant in SARS1, challenging the described recessive mode of inheritance, in a patient affected with complex spastic paraparesis with ataxia, seizures and intellectual disability. Two recent articles reported homozygous missense mutations in SARS1 also in close proximity to the active site (c.514G>A, p.Asp172Asn and c.638G>T, p.Arg213Leu), in two families affected by a neurodevelopmental syndrome including microcephaly, ataxia, seizures, moderate intellectual disability and other anomalies such as cardiomyopathy, deafness and decompensation during fever 9 10. Alterations in the central nervous system, such as MRI abnormalities including leucoencephalopathy, ataxia and seizures, have been reported in both cytoplasmic and mitochondrial ARS-related diseases 3 4 19 20…”
Section: Discussionmentioning
confidence: 99%
“…Two recent articles reported homozygous loss-of-function missense mutations in SARS1 in two independent families exhibiting a neurodevelopmental syndrome including microcephaly, intellectual disability, seizures and ataxia,9 together with other anomalies such as cardiomyopathy, deafness and decompensation during fever 10. In this work, we identified a de novo inherited novel pathogenic variant of SARS1 causing a complex spastic paraplegia and ataxia phenotype, thus confirming the recent implication of mutations in this gene in neurological and movement disorders 9 10. Furthermore, this variant illustrates the concept that dominant negative mutations in ARS genes can give rise to phenotypes similar to those caused by recessive mutations, rather than the neuropathies frequently linked to dominantly inherited variants.…”
Section: Introductionmentioning
confidence: 99%
“…NEDMAS (NEDMAS syndrome; 617709) is an extremely rare disorder described only in two families (Musante et al , 2017; Ravel, et al , 2021). The syndrome is characterized by thin body habitus, microcephaly, seizures, ataxia, muscle weakness, speech impairment, aggressive behavior, and moderate ID.…”
Section: Discussionmentioning
confidence: 99%